Association of HbA1C and comfort with diabetes self-management among adolescents and young adults with type 1 diabetes - Onwukwe, Obichi; Lundgrin, Erika L. (Frontiers in Clinical Diabetes and Healthcare, 2024)
IntroductionAdolescents and young adults (AYA) living with type 1 diabetes (T1D) are a vulnerable demographic at risk for sub-optimal glycemic outcomes at a time when they are taking over their diabetes management. The purposes of this study were to examine levels of self-reported comfort with diabetes management tasks among AYA living with T1D and to describe the relationships among comfort levels, sociodemographic factors, and HbA1c. MethodsDuring a routine diabetes care visit, AYA aged 15–23 years old living with T1D received a transition survey to self-assess their comfort level with different diabetesmanagement tasks. ResultsAmong 161 participants who completed the survey (median age 17 years, median diabetes duration 7 years, 82.3% White, 40.9% female, 66.5% with private insurance, and median HbA1c 8.8%), comfort with diabetes management tasks was generally rated highly (median overall comfort level of 4.5 out of 5), irrespective of race or insurance type. Regression analysis revealed that higher self-reported comfort level with diabetes management tasks was associated with a higher HbA1c (p = 0.006), after controlling for age, sex, race, insurance type, and diabetes duration. DiscussionThese findings suggest that self-reported comfort with independently managing T1D may not be a sufficient metric in assessing AYA patients’ need for further intervention to optimize glycemic outcomes as they transition from pediatric to adult diabetes care, and highlights the importance of continuity of care to support diabetes management during this transitional period.